Verzwegen verlangen : een geschiedenis van homoseksualiteit in België - Dupont, Wannes; Hofman, Elwin; Roelens, Jonas (Antwerpen : Uitgeverij Vrijdag, 2017)
Fonds Suzan Daniel (FSD)
Nederlands
Monografie